MODELING OF CAREER CHOICE BEHAVIORS IN INDONESIAN DENTISTRY STUDENTS - Fianirazha Primesa Caesarani; Febby Astria; Rizma Adlia Syakurah; Bertha Aulia; Reynold Siburian (Universitas Baiturrahmah, 2020)
The increasing number of dentists shows that this profession is one of the most popular career choices in Indonesia. The type of dentist professional development varies so that career planning is an important thing that has a big influence on one's future. The social-cognitive career theory (SCCT) perspective explains that there is a relationship between career self-efficacy, career outcome expectation, career intention and career exploration in the career selection process. By using SCCT, this study aimed to determine the career exploration-related behavior relationship, which consists of career self-efficacy, career outcome expectations, career intention and career exploration, in the career determination for dentistry students in Indonesia. This research is an observational analytic study of 505 samples of undergraduate and profession students of dentistry who have filled out an online questionnaire from March to June 2019. An online questionnaire consisting of a Career Decision Making Self-Efficacy-Short Form (CDMSE-SF), Career Decision Outcome Expectation (CDMOE), Career Exploration Planning or Intention Questionnaire (CEPI), Career Exploration Survey-Revised (CES-R), which has translated and validated. All models are analyzed using the maximum possible estimation of the AMOS application. This research showed that there was a significant relationship between having a career plan and father's job. This study concluded that self efficacy, outcome expectation, and career intention influence the career exploration of dentistry students significantly both directly and indirectly.